Optimization of Patient Bed Component Design Using Modeling of Motion Mechanisms on Lifting Elements Electric Patient Bed Manufacturing Case As Per ISO 13485 - Syarief, Ali; Susanto Sudiro (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2025)
Electric hospital beds are essential medical devices used in healthcare facilities to enhance patient comfort and ease caregiving tasks for medical staff. One of the key components ensuring their functionality is the lifting mechanism, which allows adjustments to the bed’s position and height according to patient needs. The main challenge in developing this mechanism lies in designing a system that is safe, stable, efficient, and compliant with international standards such as ISO 13485:2016. This study aims to optimize the lifting mechanism through a motion modeling approach. The motion modeling process involves analyzing the kinematics and statics of the mechanism, deriving equations of motion, and identifying optimal design parameters. To support this, a software-based simulation application was developed to visualize motion and calculate critical parameters such as crank angles, link lengths, and aktuator forces. Testing was conducted to ensure the mechanism met safety and performance standards. This included load testing up to 250 kg and lifecycle simulations of up to 50,000 operation cycles. The results demonstrated that the optimized lifting mechanism design meets the required safety, efficiency, and reliability standards. This research contributes to the development of electric hospital beds with more precise, safe, and reliable lifting mechanisms that adhere to international standards